The Amazing Evolutionary Complexity of Eukaryotic Tubulins: Lessons from Naegleria and the Multi-tubulin Hypothesis - Fulton, Chandler (Frontiers in Cell and Developmental Biology, 2022)
The multi-tubulin hypothesis proposed in 1976 was motivated by finding that the tubulin to build the flagellar apparatus was synthesized de novo during the optional differentiation of Naegleria from walking amoebae to swimming flagellates. In the next decade, with the tools of cloning and sequencing, we were able to establish that the rate of flagellar tubulin synthesis in Naegleria is determined by the abundance of flagellar α- and β-tubulin mRNAs. These experiments also established that the tubulins for Naegleria mitosis were encoded by separate, divergent genes, candidates for which remain incompletely characterized. Meanwhile an unanticipated abundance of tubulin isotypes has been discovered by other researchers. Together with the surprises of genome complexity, these tubulin isotypes require us to rethink how we might utilize the opportunities and challenges offered by the evolutionary diversity of eukaryotes.